[Rezension von: Roth, Dieter T., 1975-, The Parables in Q] - Tönsing, Gertrud; Roth, Dieter T. 1975- (2019)
This book presents a study of the parables in Q, which is a large and complex subject. To make it manageable, the author has taken several decisions.Firstly, the book covers all texts that are contained in the double tradition, sometimes also those that have a Markan version if the version in Matthew and/or Luke is significantly different. It includes all the parabolic texts, whether they are longer narratives or short sayings, which are often called \"similes\" or \"metaphors\" rather than parables. The book makes no attempt to classify parables in different subgenres.
Keywords: Bible. New Testament; Nonfiction; PARABLES in Q, The (Book); Q hypothesis (Synoptics criticism); ROTH, Dieter T; Rezension